2017
DOI: 10.1136/bcr-2017-219481
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome in association with antitumour necrosis factor therapy: a case of mistaken identity

Abstract: Guillain-Barré syndrome (GBS) is an immune-mediated disease characterised by evolving ascending limb weakness, sensory loss and areflexia. Two-thirds of GBS cases are associated with preceding infection. However, GBS has also been described in association with antitumour necrosis factor (TNF) therapies including infliximab and adalimumab for chronic inflammatory disorders such as rheumatoid arthritis, ankylosing spondylitis and inflammatory bowel disease. We present the case of a patient who developed GBS whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…The inflammatory reaction can then initiate GBS by activating the immune pathway. 8 In this study, we found that expression levels of IL-6, CRP, and TNF-a in the peripheral blood of patients with GBS were significantly higher than those in the healthy group, indicating that inflammatory cytokines participate in GBS, a conclusion similar to that found by Liu. 9 GBS is widely recognized as an immunoreactive disease.…”
Section: Discussionsupporting
confidence: 84%
“…The inflammatory reaction can then initiate GBS by activating the immune pathway. 8 In this study, we found that expression levels of IL-6, CRP, and TNF-a in the peripheral blood of patients with GBS were significantly higher than those in the healthy group, indicating that inflammatory cytokines participate in GBS, a conclusion similar to that found by Liu. 9 GBS is widely recognized as an immunoreactive disease.…”
Section: Discussionsupporting
confidence: 84%
“…The above genes may be a novel target for GBS treatment. For example, the relationship between TNF and GBS has been reported in a number of studies, showing that it is highly related to the inflammatory response of GBS, and there have been case reports claiming that anti-TNF therapy may trigger the occurrence of GBS (22). All types of GBS have been reported to have increased serum levels of TNF-α (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the patient has a history of autoimmune disease, which is a recognized risk factor for the development of PRES [ 20 ]. It is equally important to address the association of infliximab with GBS; however, it is less likely the cause in this case given the fact that the patient had her last infliximab dose 3 months prior to her neurological manifestations [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that our patient had taken a TNF inhibitor (infliximab) 3 months before her neurologic symptoms, it is important to address the possible correlation between TNF inhibition and GBS. There are very few published cases that have reported on this clinical situation; however, discontinuation of TNF inhibitor therapy has correlated with improvement in neurologic symptoms in most cases [ 26 , 27 , 28 ]. Our patient’s GBS was unlikely to have been caused directly from her ongoing treatment, but it is possible that her GBS was related to immune reconstitution while her TNF inhibitors had recently been stopped.…”
Section: Discussionmentioning
confidence: 99%